Trends in practice and outcomes from 2011 to 2015 for surgical aortic valve replacement: an update from the German Aortic Valve Registry on 42 776 patients. (27th November 2017) - Fujita, Buntaro; Ensminger, Stephan; Bauer, Timm; Möllmann, Helge; Beckmann, Andreas; Bekeredjian, Raffi; Bleiziffer, Sabine; Schäfer, Elke; Hamm, Christian W; Mohr, Friedrich W; Katus, Hugo A; Harringer, Wolfgang; et al.
Abstract: OBJECTIVES: Surgical aortic valve replacement (sAVR) is coming under close scrutiny with the recent upswing in the use of less invasive approaches. The aim of this analysis was to identify current trends in patient selection, procedural characteristics and outcomes after sAVR in Germany. METHODS: We analysed data from 42 776 patients included in the German Aortic Valve Registry who underwent sAVR with and without coronary artery bypass surgery (CABG) between 2011 and 2015. Baseline, procedural and short-term outcome parameters were analysed. RESULTS: Of all registered patients, 26 618 (62.2%) underwent isolated sAVR and 16 158 (37.8%) sAVR + CABG. The median age was 72 years, and the median Society of Thoracic Surgeons Predicted Risk of Mortality (STS PROM) was 2.3%. From 2011 to 2015, there was a decline in STS PROM (2.4–2.2%, P < 0.001) and a decline in risk factors, such as pulmonary hypertension (9.1–3.2%, P < 0.001), occlusive arterial disease (19.6–17.7%, P = 0.003), mitral regurgitation ≥2° (10.6–7.6%, P < 0.001) and New York Heart Association Class III/IV (65.3–59.2%, P < 0.001). In-hospital mortality was 2.3%, 1.3% had disabling stroke, 0.4% residual aortic regurgitation ≥2°, and the incidence of new-onset pacemaker/implantable cardioverter–defibrillator implantation was 3.9%. There was an increase in the use of biological valves in patients <65 years (50.1–65.7%, P < 0.001), and the proportion of rapid deployment valves increased significantly (1.5–8.4%, P < 0.001) over the investigated time period. CONCLUSIONS: Both isolated sAVR as well as sAVR + CABG resulted in excellent in-hospital outcomes based on >42 000 patients treated between 2011 and 2015. The implementation of alternative treatment strategies has resulted in palpable changes in patient and device selection.